Ambiências na parede: concepções espaciais em pintura e desenho - Nunes, Michele Martins (2010)
This master degree dissertation consider the individual plastic production entitled Ambiences on the Wall, composed of eight works that were produced during the masters course. The plastic proposal starts in perceptions of a particular universe (home-intimacy), seeking its re-development through the creative process, bringing to the same level the relations between painting and drawing, color and achromatic, perennial and ephemeral, memory and present, real and fantastic. In these works, the house's rooms are represented by painting with nuances of gray and by black lines installed on white walls. Opposed to these scenarios are superimposed colored pictures, composed of appropriated elements of cubism. The visual poetic investigation starts on the establishment of these works, focusing on different conceptions of space that they suggest: the represented spaces, the relationship with the common space and the perceptions of the house s environments. First is presented the proposal, which seeks to combine oil painting on canvas and drawing on the wall with adhesive. The text deals with the representational systems that are chosen for such combination, and with the counterpoint chromatic x achromatic that the works present. Later, aspects of the works are considered, and also its relationship with the space around it. Finally, the text discusses the thematic issues related to the represented spaces and the figures that inhabit them.